Rancangan Strategi Promosi Kesehatan Masyarakat untuk Meningkatkan Perilaku Masyarakat dalam Menggunakan Jamban Sehat - Desi Irma Santi; Budi Waskito (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The low utilization of sanitary latrines remains a major challenge in efforts to improve public health status. Open defecation behavior is influenced by various factors, including levels of knowledge, attitudes, socio-economic conditions, and the effectiveness of health promotion activities that have not yet been optimal. This study aims to analyze community health promotion strategies in improving behavioral practices related to the use of sanitary latrines. This research employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews with community members, health cadres, and primary health center (puskesmas) staff selected using purposive sampling. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of the research findings. The results indicate that existing health promotion activities have not been fully effective due to limited media utilization, less interactive delivery methods, and economic constraints faced by the community. Informants suggested the use of visual media, hands-on practice, and direct demonstrations of sanitary latrines to improve community understanding and message retention; however, implementation of these methods is constrained by financial limitations. SWOT analysis highlights the need to strengthen health promotion strategies by leveraging local potential and enhancing cross-sectoral support. The findings conclude that participatory, contextual, and socio-economically adaptive health promotion plays a crucial role in encouraging behavioral change toward the consistent use of sanitary latrines. Furthermore, a SWOT-based health promotion strategy is expected to serve as a practical reference for accelerating behavioral change toward the elimination of open defecation practices.